Changes in histologic and biochemical indexes of bone turnover after bilateral nephrectomy in patients on hemodialysis. Evidence for a possible role of endogenous calcitonin. - Kanis, J; Earnshaw, M; Heynen, G; Ledingham, J; Oliver, DO; Russell, G; Woods, C; Franchimont, P; Gaspar, S (1977)
We studied the effects of bilateral nephrectomy on bone metabolism in 27 patients on maintenance hemodialysis. After nephrectomy plasma alkaline phosphatase fell rapidly in 10 patients whose preoperative plasma levels had been higher than normal. This fall was associated with a transient decrease in osteoblast counts of iliac-bone biopsies. A fall in plasma phosphate and a rise in plasma immunoreactive calcitonin also occurred, but calcium and immunoreactive parathyroid hormone levels did not change. Alkaline phosphatase levels remained unchanged in a control group of 17 patients on dialysis who had undergone an operation other than nephrectomy. In 26 nonsurgical patients on dialysis, immunoreactive calcitonin was inversely related to osteoblast counts. Rises in immunoreactive calcitonin may be partly responsible for the transient decreases in bone turnover after bilateral nephrectomy. Low levels of endogenous calcitonin may allow an increase in bone turnover in chronic renal failure.